2019
DOI: 10.3988/jcn.2019.15.3.339
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of a Contribution of the Vestibular System to Frequent Falls in Progressive Supranuclear Palsy

Abstract: Background and Purpose Conflicting results about vestibular function in progressive supranuclear palsy (PSP) prompted a systematic examination of the semicircular canal function, otolith function, and postural stability. Methods Sixteen patients with probable PSP [9 females, age=72±6 years (mean±SD), mean disease duration=3.6 years, and mean PSP Rating Scale score=31] and 17 age-matched controls were examined using the video head impulse test, caloric testing, ocular an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(42 citation statements)
references
References 25 publications
3
20
0
17
Order By: Relevance
“…Our results confirm previous reports underlining reduced saccade peak velocity, saccade amplitude and impaired gain of SPEM in patients suffering from PSP-P and PSP-RS compared to healthy controls (19,20). We could not detect impairment of semicircular-canal function examined at 0.32 Hz sinusoidal rotation in our patients with PSP (21). Square wave jerks have been described to occur in the early stage of PSP which was also observed in our cohort (22).…”
Section: Discussionsupporting
confidence: 91%
“…Our results confirm previous reports underlining reduced saccade peak velocity, saccade amplitude and impaired gain of SPEM in patients suffering from PSP-P and PSP-RS compared to healthy controls (19,20). We could not detect impairment of semicircular-canal function examined at 0.32 Hz sinusoidal rotation in our patients with PSP (21). Square wave jerks have been described to occur in the early stage of PSP which was also observed in our cohort (22).…”
Section: Discussionsupporting
confidence: 91%
“…It is in line with an earlier study of Liao et al, which reported reduced cVEMP amplitudes in 10 PSP patients compared to 30 controls, and suggested that impaired vestibulo-spinal reflexes contributed to postural instability in PSP (14). While Liao et al also measured reduced oVEMP amplitudes in PSP, other groups failed to confirm VEMP abnormalities in PSP (26,27). Moreover, although cVEMP and oVEMP scores did not differ in PD patients with and without a complaint of imbalance, we found delayed oVEMP latencies in those with imbalance.…”
Section: Discussionsupporting
confidence: 90%
“…In the first selection phase, the titles and abstracts of the identified studies were evaluated, and only 21 of them addressed the study theme of this literature review. These publications were read in full and, after application of the eligibility criteria, 18 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) were selected to compose the final sample of this study. Figure 1 shows the detailed selection process of these publications.…”
Section: Resultsmentioning
confidence: 99%
“…From the information extracted from the 18 selected articles (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) , a chart was created including data on disease, vestibular symptoms, and results of the vHIT and oculomotor tests (Chart 1).…”
Section: Resultsmentioning
confidence: 99%